German Productivity - A Reassessment via the New Ifo Productivity Database - Andreas Kuhlmann (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2006)
A detailed analysis of the German productivity development is indispensable for understanding, why Europe is lagging behind the US growth since the mid 1990s. In this paper a new and unique database is used to analyze the sources of German productivity growth since 1970. It is shown that investment in information and communication technology (ICT) played a minor role in the German productivity development. The results include detailed descriptive statistics and projections for output and labor productivity growth for the coming decade. The base-case projection puts overall trend output growth at 1.53 percent per year over the next decade. Average labor productivity will grow at an annual rate of 1.59 percent.
Keywords: F43; O47; R11; 330; Growth accounting; productivity analysis; TFP